GAMBARAN BAYI BARU LAHIR DARI IBU YANG TERKAIT COVID-19 DI RSUD R.A.A TJOKRONEGORO KABUPATEN PURWOREJO: GAMBARAN BAYI BARU LAHIR DARI IBU YANG TERKAIT COVID-19 - Sholichah, Nur; Dyah Anggraeni, Nabilah (Jurnal Komunikasi Kesehatan, 2023)
Background: Based on a preliminary study at RSUD RAA Tjokronegoro Kabuptaen Purworejo, there are more newborns whose RT-PCR results show negative results from mothers related to covid-19 than babies whose RT-PCR results show positive results. Research Objectives: Knowing the Picture of Newborns from Mothers Related to Covid-19 at RSUD R.A.A Tjokronegoro, Purworejo Regency.Research Methods: This type of research is a descriptive researcher using a retrospective approach method. With a population of 145 respondents and a sample of 145 respondents. In this study using the total sampling technique. The study was conducted from October 2021 to October 2022. In this study, it only used univariate analysis.Research Results: the most respondents with female sex were 79 (54.5%), and RT-PCR results showed negative 135 (93.1%). Conclusion: The respondents whose RT-PCR results were the most were negative 135 (93.1%), Keywords : Newborns of mothers related to covid-19